KINERJA GURU PADA SEKOLAH DASAR NEGERI DI KELURAHAN SIDOMULYO TIMUR KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Nanda Kasih Pratiwi; Dadang Mashur (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
SD Negeri 112 Pekanbaru and SD Negeri 161 Pekanbaru are basic education units located in the Sidomulyoa Timur Village, Marpoyan Damaia District, Pekanbaru City. The theoretical concept used in this study is the theory of According to Robbins (2006), measuring employee performance individually. The method used in this research is an qualitative method by using a descriptive approach. The data collection technique used is by using interview and documentation techniques. The purpose of this research is to find out the performance of teachers at public elementary schools in Sidomulyo Timur Village, Marpoyan Damai District, Pekanbaru City, and to find out the factors that hinder teacher performance at public elementary schools in Sidomulyo Timur Village, Marpoyan Damai District, Pekanbaru City. The results of the study found that the performance of teachers at State Elementary Schools in Sidomulyo Timur Village, Marpoyan Damai District, Pekanbaru City was not optimal. The factors that hinder the performance of teachers at State Elementary Schools in Sidomulyo Timur Village, Marpoyan Damai District, Pekanbaru City are the ability and expertise of teachers, limited resources, and awards. To improve the performance of teachers at State Elementary Schools in Sidomulyo aTimura Village, Marpoyan Damai District, Pekanbaru City, all teachers, especially teachers at SD Negeri 112 Pekanbaru and SD Negeri 161 Pekanbaru, need to improve their respective abilities and expertise, in addition to the related Dinar and the Principal need to add school resources that still do not meet school needs and need to improve teacher welfare, as a form of appreciation for improving teacher performance at State Elementary Schools in East Sidomulyo Village, Marpoyan Damai District, Pekanbaru City.